A Comprehensive Review on Anticancer Potential of Pulicaria Plants and their Derivatives - Barabadi, Tahere; Rahimi, Hossein; Mohamadi-Zarch, Seyed Mahdi; Bagheri, Seyyed Majid (Current Cancer Drug Targets, 2025)
The genus Pulicaria, belonging to the Asteraceae family, includes 100 species distributed from Europe to North Africa and Asia, especially around the Mediterranean. A number of extracts and compounds of this genus have been found to have anticancer effects on various cancer cell lines. Google, PubMed, Web of Science and Scopus databases were searched for articles related to Pulicaria or its isolated compounds. The search was conducted using various keywords, including “Pulicaria and anticancer activity”. After the review, the relevant articles were summarized and included in the review article. Fortunately, the results of this review showed that relatively comprehensive studies have been conducted in this field, and the presence of various compounds in these plants can be used in cancer research. The results of our review showed that Pulicaria vulgaris has the strongest effect and Pulicaria dysenterica has the weakest effect on cancer cells. Future studies should focus on finding purer compounds and investigating the anticancer effects of these compounds. These herbal compounds can also be used alongside standard drugs to treat cancer, especially to reduce the effect of drug resistance.
Keywords: isolated compounds